2498. Association of Increasing Age With Hospitalization Rates, Clinical Presentation, and Outcomes Among Older Adults Hospitalized With Influenza—US Influenza Hospitalization Surveillance Network (FluSurv-NET). (26th November 2018) - Czaja, Christopher; Miller, Lisa; Alden, Nisha; Wald, Heidi; Cummings, Charisse Nitura; Rolfes, Melissa; Garg, Shikha; Anderson, Evan J; Bennett, Nancy M; Billing, Laurie; Chai, Shua J; Eckel, Seth; et al.
Abstract: Background: Few data describe the epidemiology of influenza among adults ≥65 years old according to age strata. We evaluated age-related differences in influenza-associated hospitalization rates, clinical presentation, and outcomes among older adults at 14 FluSurv-NET sites during the 2011–2012 through 2014-2015 influenza seasons. Methods: Study patients were hospitalized ≤14 days after and ≤3 days before a positive influenza test. Age strata were 65–74, 75–84, and ≥85 years old. We adjusted hospitalization rates for under detection and assessed for age-related trends in risk factors and symptoms. We used logistic regression to calculate odds ratios (OR) for pneumonia and in-hospital death adjusted for season, sex, nursing home residence, smoking, medical comorbidities, influenza vaccination, and study site. Results: There were 19, 760 patients, including 5, 956 aged 65–74 years, 6, 998 aged 75–84 years, and 6, 806 aged ≥85 years. There was a stepwise increase in hospitalization rates with age (figure). Increasing age was positively associated with female sex, nursing home residence, neurologic disorder, cardiovascular and renal disease, and vaccination, and inversely associated with morbid obesity, smoking, asthma, chronic metabolic disease, and immunosuppression ( P < 0.01). Among 10, 548 (53.3%) patients with symptom data from 2014 to 2015, increasing age was associated with a higher prevalence of altered mental status and lower prevalence of fever, myalgias, respiratory or gastrointestinal symptoms, and headache ( P ≤ 0.01). Compared with 65–74 year olds, older patients had a higher risk of pneumonia (≥85 year-olds: OR 1.2, 95% CI 1.0, 1.3, P = 0.01) and death (75–84 year olds: OR 1.4, 95% CI 1.2, 1.7, P < 0.01; ≥85 year-olds: OR 2.1, 95% CI 1.7, 2.6, P < 0.01). Conclusion: There are age-related differences in the epidemiology, clinical presentation, and outcomes of older adults hospitalized with influenza. These may reflect differences in health status and healthcare provider practice patterns. Public health epidemiologists should consider using additional age strata in ≥65 year-olds when analyzing influenza surveillance data. Clinicians should be aware that influenza among the oldest adults may present atypically and that mortality is increased. Disclosures: E. J. Anderson, NovaVax: Grant Investigator, Research grant. Pfizer: Grant Investigator, Research grant. AbbVie: Consultant, Consulting fee. MedImmune: Investigator, Research support. PaxVax: Investigator, Research support. Micron: Investigator, Research support. W. Schaffner, Merck: Member, Data Safety Monitoring Board, Consulting fee. Pfizer: Member, Data Safety Monitoring Board, Consulting fee. Dynavax: Consultant, Consulting fee. Seqirus: Consultant, Consulting fee. SutroVax: Consultant, Consulting fee. Shionogi: Consultant, Consulting fee.